The Effect of Platelet-Rich Fibrin (PRF) in Accelerating Periodontal Regeneration: A Randomized Controlled Clinical Trial - Ashwini Dhopte; Konsam Bidya Devi; KS Pandaw; Anamika Rani; Sachin Chand; Hiroj Bagde (Journal of Pharmacy and Bioallied Sciences)
Background: Regeneration of periodontal tissues is an essential component in treating periodontal disease, and there is an increasing focus on biological agents that might improve the healing process. Materials and Methods: The randomized controlled clinical study included a cohort of 60 individuals diagnosed with chronic periodontitis. Each participant was randomly allocated to one of two groups: the experimental group (n = 30), which underwent PRF in combination with traditional open flap debridement (OFD), and the control group (n = 30), which received OFD alone. Clinical criteria such as probing pocket depth (PPD), clinical attachment level (CAL), and bone fill percentage were assessed at baseline and after 6 months. Furthermore, cone-beam computed tomography (CBCT) was used to evaluate bone regrowth radiographically. Results: Following a period of 6 months, the experimental group had a notable decrease in postpartum depression (mean decrease of 4.2 mm) and an increase in central artery ligation (mean increase of 3.5 mm) compared to the control group, which had a mean decrease in postpartum depression of 2.8 mm and a mean increase in central artery ligation of 2.1 mm. The test group had a notably greater proportion of bone fill (45%) in comparison to the control group (30%). Further radiographic study verified enhanced bone regeneration in the areas treated with PRF. Conclusion: The use of Platelet-Rich Fibrin (PRF) in combination with traditional periodontal surgery greatly expedites the process of periodontal regeneration, as shown by notable enhancements in clinical indicators and bone regeneration.